THEORETICAL ASPECTS OF THE DIGITAL ECONOMY AND ITS IMPORTANCE IN THE TOURISM SECTOR OF UZBEKISTAN - Bekmurodov Bakhtiyor , Farkhodovich (THE INNOVATION ECONOMY, 2025)
This research is dedicated to an in-depth exploration of the theoretical foundations of the digital economy and an analysis of its pivotal role in the development of tourism in Uzbekistan. The application of key components of the digital economy, including big data analytics, artificial intelligence, and blockchain technology, in the tourism sector is examined through international case studies. Leveraging Uzbekistan’s rich cultural-historical heritage and tourism potential, the study evaluates the possibilities of adapting digital technologies to local conditions. The research aims to underscore the importance of digitalization in enhancing the economic efficiency of tourism, improving service quality, and ensuring global competitiveness. Additionally, it addresses challenges such as local infrastructure limitations and the level of digital literacy among the population